2004
DOI: 10.1590/s1519-566x2004000400010
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of mass multiplication of Telenomus podisi Ash. and Trissolcus basalis (Woll.) (Hymenoptera: Scelionidae) on eggs of Euschistus heros (Fab.) (Hemiptera: Pentatomidae)

Abstract: . In a first experiment, egg masses randomly distributed were shown the most adequate method of exposure of E. heros to parasitism. In a second experiment, egg masses of E. heros were randomly glued on cardboard cards and exposed to parasitism by T. podisi and T. basalis. The parasitoids multiplied on E. heros eggs showed parasitism (ca. 99%) similar to that observed with T. basalis reared on N. viridula eggs (99.7%). Emergence rates were higher than 80% for T. podisi and T. basalis multiplied on E. heros eggs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 11 publications
0
27
0
4
Order By: Relevance
“…Thus, this study aimed to assess the selectivity of pesticides registered for soybean crop on the stink bug egg parasitoids T. podisi and T. basalis in adult stage. Peres & Corrêa-Ferreira (2004), was used.…”
Section: Abstract Resumomentioning
confidence: 99%
“…Thus, this study aimed to assess the selectivity of pesticides registered for soybean crop on the stink bug egg parasitoids T. podisi and T. basalis in adult stage. Peres & Corrêa-Ferreira (2004), was used.…”
Section: Abstract Resumomentioning
confidence: 99%
“…Jones & Westcott () demonstrated that 2.1% of females and 13.5% of males remained alive after 60 days when Trissolcus basalis Wollaston (Hymenoptera: Platygastridae) were given honey and water. Access to honey in laboratory has been found to benefit T. podisi as well, by enhancing their longevity and fecundity over that of water‐fed individuals (Yeargan, ; Peres & Corrêa‐Ferreira, ).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of feeding this species can cause signifi cant losses in yield, quality and germination potential of grains (PANIZZI & SLANSKY-JÚNIOR, 1985;PANIZZI et al, 2000a;CORRÊA-FERREIRA & AZEVEDO, 2002; on its biology, ecology and behavior in order to develop effective control tactics (SILVA et al, 2011;PANIZZI, 2013). Thus, rearing and maintaining phytophagous stink bugs in the laboratory is important to allow the conduction of biology tests, resistant strains tests, effi cacy of insecticides, use in biological control programs with parasitoids, identifi cation of pheromones, among others (CORRÊA-FERREIRA, 2002;PEREZ & CORRÊA-FERREIRA, 2004;GODOY et al, 2005;SILVA et al, 2011).…”
Section: Introductionmentioning
confidence: 99%